Evaluation of the application of hospital management information system using the hot-fit method - Anjlya Agustin; Rapotan Hasibuan (Malahayati International Journal of Nursing and Health Science, 2023)
Background: The hospital management information system (SIMRS) is an important part of supporting health service decisions, so it is necessary to pay attention to its sustainability. SIMRS in Aek Kanopan, North Labuhanbatu found obstacles in the form of errors and delays in sending data, resulting in incomplete monthly reports.Purpose: This research is aimed at knowing the implementation and at the same time evaluating the SIMRS hospital management information system at Aek Kanopan Hospital by looking at the human, organizational and technological aspects of the net benefit (hot-fit).Method: Quantitative study with cross-sectional design, data collection was collected through interviews and questionnaires, with a sample population of 31 people, and data were analyzed univariate and multivariate with multiple linear regression tests.Results: Based on the results obtained from the characteristics of the respondents, univariate analysis and multiple regression analysis it can be concluded that the user's perception of the human aspect of the net benefit variable is said to be good, the same is true of the organizational aspect of the net benefit variable is also good, and for the perception of the technological aspect of the net benefit variable is said to be good. This research also found that human, technological and organizational variables on net benefits have a significant effect on net benefits togetherConclusion: It can be concluded that there is a good relationship between human, technology, and organization variables on net benefits